2013
DOI: 10.1039/c3cc46863a
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometry-controlled FeP nanoparticles synthesized from a single source precursor

Abstract: Phase-pure FeP nanoparticles (NPs) have been synthesized through low temperature thermolysis of the single source precursor [(CO)4Fe(PH3)]. Examination of the mechanism demonstrates the central role of the labile CO ligands and the weak P-H bonds to yield stoichiometry controlled FeP materials.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Compound 1 has been previously demonstrated to yield nanoparticles of FeP by solution-based decomposition 24 and was explored as a CVD precursor; however, it was found that Fe 2 P was the only material that deposited on a quartz substrate in our apparatus at 350 °C (Table S1) . The 31 P and 1 H NMR spectra of the off-gases from the decomposition of 1 under CVD conditions confirmed the elimination of PH 3 (Figures S2−S5).…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…Compound 1 has been previously demonstrated to yield nanoparticles of FeP by solution-based decomposition 24 and was explored as a CVD precursor; however, it was found that Fe 2 P was the only material that deposited on a quartz substrate in our apparatus at 350 °C (Table S1) . The 31 P and 1 H NMR spectra of the off-gases from the decomposition of 1 under CVD conditions confirmed the elimination of PH 3 (Figures S2−S5).…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…Recently, we investigated the usage of single‐source precursors for the synthesis of transition metal phosphide nanoparticles and could show that complexes containing only labile CO ligands and hydrogen substituents on phosphorus are suitable precursors for the synthesis of size‐ and stoichiometry‐controlled nanoparticles . This was demonstrated by the synthesis of FeP nanoparticles with a precise stoichiometry control by starting from the single‐source precursor [Fe(CO) 4 (PH 3 )] or [{Fe(CO) 3 } 2 (μ‐PH 2 )] 2 . Targeting the corresponding As‐containing complexes, we realized that the synthetic pathway for this kind of compounds goes totally different ways and, to our surprise, we achieved the synthesis of the unprecedented diarsene iron carbonyl complex [Fe(CO) 4 (η 2 ‐As 2 H 2 )] ( 2 )—a complex without sterically demanding ligands—in which the diarsene ligand is only stabilized in the coordination sphere of one transition metal.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, under similar reaction conditions, the methanolysis of [{Fe(CO) 4 }P(SiMe 3 ) 3 ] leads to [{Fe(CO) 4 }(PH 3 )] in good yields. Thermolysis or photolysis of [{Fe(CO) 4 }(PH 3 )] lead to the formation of the dinuclear complex [{Fe(CO) 3 } 2 (μ‐PH 2 )] 2 , indicating that the hypothetical complex [Fe(CO) 4 (AsH 3 )] might form as an intermediate, which, however, is unstable and decomposes to 2 and other unidentified products.…”
Section: Methodsmentioning
confidence: 99%
“…Cd 3 P 2 NCs could be synthesized by TOP (Khanna et al, 2010), PH 3 (Miao et al, 2012), P(SiMe 3 ) 3 (Miao et al, 2010), and MSCs (Li et al, 2014) acting as single source precursors. FeP could be synthesized by TOP (Henkes and Schaak, 2007) and (CO) 4 Fe(PH 3 ) (Hunger et al, 2013) acting as single source precursors. Copper phosphides could be synthesized by TOP (Henkes and Schaak, 2007), PH 3 (Manna et al, 2013), P(SiMe 3 ) 3 (Liu et al, 2016), and P 4 (Bichat et al, 2004a).…”
Section: Introductionmentioning
confidence: 99%